2019
DOI: 10.3748/wjg.v25.i30.4246
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease patient profiles are related to specific information needs: A nationwide survey

Abstract: BACKGROUND Inflammatory bowel diseases (IBD) is a heterogenous, lifelong disease, with an unpredictable and potentially progressive course, that may impose negative psychosocial impact on patients. While informed patients with chronic illness have improved adherence and outcomes, previous research showed that the majority of IBD patients receive insufficient information regarding their disease. The large heterogeneity of IBD and the wide range of information topics makes a one-size fits all knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 23 publications
0
41
0
1
Order By: Relevance
“…This finding is supported by studies in irritable bowel syndrome, which have found that the type, amount, and source of information desired by patients depend on the course of the disease (i.e., active vs. remission). 39,40 Our inclusion of items on the A scale relating to the inevitability of getting DR due to aging, genetics, or fate is important, as disease-related fatalism has been reported previously in other health fields, such as cancer. 41,42 Indeed, high fatalism scores have been found to predict non-adherence to cancer screening recommendations, 42 as well as diabetes medication adherence and self-care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is supported by studies in irritable bowel syndrome, which have found that the type, amount, and source of information desired by patients depend on the course of the disease (i.e., active vs. remission). 39,40 Our inclusion of items on the A scale relating to the inevitability of getting DR due to aging, genetics, or fate is important, as disease-related fatalism has been reported previously in other health fields, such as cancer. 41,42 Indeed, high fatalism scores have been found to predict non-adherence to cancer screening recommendations, 42 as well as diabetes medication adherence and self-care.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by studies in irritable bowel syndrome, which have found that the type, amount, and source of information desired by patients depend on the course of the disease (i.e., active vs. remission). 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…There were four studies that evaluated patient perspectives and expectations at the time of diagnosis [33][34][35][36]. The conclusion from three of these studies was that patients expressed a greater need for knowledge at the time of diagnosis [34][35][36]. Table 2 outlines the study characteristics and outcomes.…”
Section: Patient Perspectives and Expectations At The Time Of Diagnosismentioning
confidence: 99%
“…In the first category of questioning about the participants' knowledge of IBD tests, participants mostly reported to not know of any test for the state of the disease. This shows that the majority of participants were uninformed, which can lead to a deterioration in the quality of life 12 . When living with a chronic disease, it is essential to know about advances in medicine, to know the signs and symptoms, and how to better diagnose and monitor the disease to improve quality of life.…”
Section: Discussionmentioning
confidence: 94%